Observation on the shapes of snow crystals in the summer season in Mizuho Plateau, Antarctica - Satow, Kazuhide (1983)
P(論文) Snow crystal observations in Mizuho Plateau, Antarctica, during the 1981 austral summer revealed the following : The shapes of single bullet and combination of bullets were frequently observed, and because of their large mass, these crystals are considered to be the major contributor to the snow accumulation in this area. Long solid column crystals were found within the surface air temperature range from -42℃ to -56℃, when the air temperature at the inversion top was from -38℃ to -43℃. The mean length of c-axis of these crystals was 287μm and the maximum length was 1.2mm. The mean value of the axial ratio (c/a) of the crystals was 18 and the maximum value was 70. Only a few scalene hexagonal, triangular and square form crystals were detected in the inland. departmental bulletin paper